2021
DOI: 10.1136/bmjopen-2021-055126
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and short-term outcomes of RT-PCR- positive patients with COVID-19: a cross-sectional study in a tertiary care hospital in Dhaka, Bangladesh

Abstract: ObjectiveThe COVID-19 pandemic is still raging worldwide. While there is significant published evidence on the attributes of patients with COVID-19 from lower-income and middle-income countries, there is a dearth of original research published from Bangladesh, a low-income country in Southeast Asia. Based on a case series from a tertiary healthcare centre, this observational study has explored the epidemiology, clinical profile of patients with COVID-19 and short-term outcomes in Dhaka, Bangladesh.Design and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The literature reflects that violence in the workplace for HCWs is a long-standing and multifactorial challenge to healthcare systems across the globe with a staggering 62% prevalence of physical violence [2]. The literature further details a myriad of factors that make this phenomenon more likely, including but not limited to understaffing, inadequate security, long waiting times, lack of privacy, and anger from patients and families [3].…”
Section: Introductionmentioning
confidence: 99%
“…The literature reflects that violence in the workplace for HCWs is a long-standing and multifactorial challenge to healthcare systems across the globe with a staggering 62% prevalence of physical violence [2]. The literature further details a myriad of factors that make this phenomenon more likely, including but not limited to understaffing, inadequate security, long waiting times, lack of privacy, and anger from patients and families [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies detailed the clinical presentation of hospital-admitted reverse transcription-PCR (RT-PCR) positive patients with COVID-19, very few originate from Bangladesh and few are still from the Southeastern part of Bangladesh. [8][9][10][11][12][13][14] Therefore, the present study was undertaken to describe the clinical features and outcome and to identify the predictors of clinical outcome, as early identification would be paramount in optimal utilization of medical resources in managing these high risk-patients. According to the data of the present series median age of the hospitalized COVID-19 infected patients was 57 years which is in agreement with other studies conducted in and around our country.…”
Section: Introductionmentioning
confidence: 99%
“…Male predominance of the present study was in agreement with other studies conducted in and around our country. [9][10][11][12][13][14]19 The gender distribution was similar in survivor and non-survivor group. A preliminary Chinese study investigated the role of gender in COVID-19 and found that while males and females had the same prevalence; males had higher mortality as compared to women.…”
Section: Introductionmentioning
confidence: 99%